Perancangan Sistem Informasi Pengaduan Mahasiswa Universitas Methodist Indonesia Berbasis Web - Rini Inriani Katarina Sitanggang; Jamaluddin Jamaluddin; Roni Jhonson Simamora (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Universitas Methodist Indonesia (UMI) faces various limitations in handling student complaints, which hinder the effectiveness of problem resolution. This research aims to build a web-based student complaint information system that can accommodate and manage student complaints quickly and efficiently. The observation method is used to observe the ongoing complaint process and interactions between students and the existing complaint system. Implementation of this system begins with the creation of a database designed to store and manage complaint data, user information and other important data. The system backend was developed using PHP to handle business logic, including complaint processing, user management, and interaction with the database. As a result, this system changes the complaint management process from previously manual to more efficient and computerized, so that students can easily submit complaints, monitor status, and view complaint history. This system also allows the campus to respond to complaints more quickly and effectively.